Functional Alterations and Cerebral Variations in Humans Exposed to Early Life Stress - González-Acosta, Carlos A.; Rojas-Cerón, Christian A.; Buriticá, Efraín (Frontiers in Public Health, 2021)
Early life stress can be caused by acute or chronic exposure to childhood events, such as emotional, physical, sexual abuse, and neglect. Early stress is associated with subsequent alterations in physical and mental health, which can extend into adolescence, adulthood, and even old age. The effects of early stress exposure include alterations in cognitive, neuropsychological, and behavioral functions, and can even lead to the development of psychiatric disorders and changes in brain anatomy. The present manuscript provides a review of the main findings on these effects reported in the scientific literature in recent decades. Early life stress is associated with the presence of psychiatric disorders, mainly mood disorders such as depression and risk of suicide, as well as with the presence of post-traumatic stress disorder. At the neuropsychological level, the involvement of different mental processes such as executive functions, abstract reasoning, certain memory modalities, and poor school-skill performance has been reported. In addition, we identified reports of alterations of different subdomains of each of these processes. Regarding neuroanatomical effects, the involvement of cortical regions, subcortical nuclei, and the subcortical white matter has been documented. Among the telencephalic regions most affected and studied are the prefrontal cortex, the hippocampus, the amygdala, and the anterior cingulate cortex. Understanding the impact of early life stress on postnatal brain development is very important for the orientation of therapeutic intervention programs and could help in the formulation and implementation of preventive measures as well as in the reorientation of research targets.